The Relationship Between Serum Uric Acid at Different Concentrations of Lipid Indices and the Risk of Myocardial Revascularization in Patients With Acute Coronary Syndrome: A Retrospective Analysis - Lin, Yajuan; Hidru, Tesfaldet Habtemariam; Fan, Rui; Gao, Jinghan; Li, Han; Yang, Xiaolei; Xia, Yunlong (Frontiers in Cardiovascular Medicine, 2021)
Objective: Both serum uric acid (SUA) levels and lipid components, such as LDL, HDL, and Lp(a), have been reported to associate with CAD. However, the influence of SUA status at different concentrations of lipid indices for the risk of myocardial revascularization (MRT) in ACS patients is currently unknown. Methods: We retrospectively analyzed a hospital-based sample of 14234 ACS patients with no previous history of percutaneous coronary intervention (PCI) or coronary artery bypass graft (CABG) surgery. All patients went for coronary angiography. Binary logistic regression models were performed, and the odds ratios (OR) at 95% confidence interval (CIs) were used to approximate the associated risk of UA and lipid profile for myocardial revascularization, with the lowest quartile/ tertile serving as the reference category. Results: Overall, 8818 (61.9%) patients undergone MRT out of 14234 patients. Elevated SUA and HDL were negatively associated with an increased likelihood of MRT during admission (P<0.001). However, LDL and Lp(a) levels were positively associated with MRT among ACS patients. Furthermore, interaction analyses between SUA and lipid profiles, particularly LDL and Lp(a), compared with those in the lowest quartile of SUA levels, show that patients in higher SUA quartiles grouped by lipid components had a significantly lower chance of undergoing MRT, with the lowest OR (95%CI) for subjects being 0.222 (0.170-0.290), 0.478 (0.374-0.612), and 0.604 (0.468-0.780) in LDL tertiles, being 0.671(0.523-0.862), 0.316(0.242-0.413), and 0.410 (0.310-0.542) in Lp(a) tertiles, respectively. In the three tertiles of HDL levels, the incidence of MRT dropped steadily as SUA levels increased. Also, we further analyzed ACS patients without diabetes. Compared with the first quartile of SUA levels, the risks of MRT were significantly lower in different tertiles of lipids components (LDL, Lp(a), HDL). Conclusion: An increase in SUA levels may decrease the chance of undergoing MRT in ACS patients, even in those with increased Lp(a) and LDL-c. Elevated serum uric acid may play a protective role during an acute stage of ACS.